Assessment of ENT Residents function using 360-degree evaluation method at Shiraz University of Medical Sciences - M Shisheh-Gar; S Rivaz; M Amini; M Rivaz (Babol University of Medical Sciences, 2019)
BACKGROUND AND OBJECTIVE: Professional behaviors and communication skills residents in the traditional by faculty members evaluated, while one of the best ways to assess attitudes and behaviors is to ask people who are continually working in the workplace with residents have connection, 360- degree assessment in order to evaluate the performance of the clinical residents, a wide range of skills using multiple monitors Includes. The purpose of this study was to evaluate communication skills and interpersonal support of the ENT students of the Shiraz University of Medical Sciences using the 360-degree method. METHODS: This is a descriptive-analytic study that all ENT residents (15 people) were educated in educational in Shiraz in 2017. Questionnaires have used the performance of the residents ( including questionnaires of faculty members of the "peer" medical colleagues, nurses' cohorts, self-assessment, and patient) were prepared and adjusted. The validity of the questionnaire confirmed by experts of medical education and the reliability of the questionnaire was obtained after a preliminary study (r=0.92). the findings were then analyzed using SPSS16 software using descriptive statistics and T-test and Pearson correlation coefficient was analyzed in p≤0.05. FINDINGS: The results showed that the mean score of the evaluation scores by the assistants themselves (48.33±9.99), counterparts (52.01±5.13) and professors (66.12±5.22) the highest and the average of the patient (13.2±23.32) & nurses (31.2±6.86) was the lowest. CONCLUSION: The results indicate that the evaluation should not be limited to a group of contacts, but for a more comprehensive assessment, it is necessary to involve different groups in the evaluation process.